Screening Of Fungal Pathogens For Biocontrol Of Water Hyacinth (Eichhornia Crassipes (MART.)Solms) - Santhy Kammath S (Department of Plant Pathology, College of Agriculture, 1994)
A survey was conducted in and around Trivandrum district viz., in veli, Ambalathara and Akulam to obtain the fungal pathogens of water hyacinth for its biocontrol. Colletotrichum gloeosporioides (Penzig) Penzig and Sacc Curvularia lunata (Wakker) Boedjin, Fusarium equiseti (Corda) sacc., Fusarium semitectum Berk and Rav, Fusarium solani (Mart) sacc., R. solani Kuhn and sterile fungus were found infecting the plants. The seasonal occurrence of the fungi isolated was studied and it was found that Fusarium spp. were present throughout the period of study. C. gloeosporioides and R. solani were present in the rainy season only. The pathogenicity of all the above fungi to the water hyacinth plants was established by artificial inoculation. Host range studies revealed that R. solani had a wide host range, which included amaranthus, cowpea, rice Monochoria vaginalis and panicum repens. The host range of C. gloeosporioides included chilli, Commelina benghalensis, Hydrocotyl asiatica and Ludwigia parviflora Fusarium spp. were found to infect Monochoria vaginalis only. Among the fungal pathogens isolated from water hyacinth, F. semitectum caused highest intensity of infection of 51.10 per cent followed by F. equiseti and F. solani (48.88 per cent) C. gloeosporioides and R. solani caused 44.44 and 45.76 per cent intensity of infection respectively. Curvularia lunata caused the lowest intensity of infection of 20 per cent. An experiment was conducted to fix the concentration of inoculam required for effective destruction of water hyacinth. The spore concentration of 10 9 spores/ml was the most effective one in the case of F. equiseti, F. semitectum and F. solani For C. gloeosporioides spore concentration of 2 x 109 sporce/ml was the most effective one. Different carrier materials were tried for mass multiplication and storage of the promising fungal pathogens of water hyacinth. The different carrier materials tested were coir pith, paddy straw, peat moss, rice bran and wheat bran. Wheat bran was found to be the most suitable media for F. equiseti, F. semitectum and F. solani. In wheat bran, the spore count and viability of the spores of these fungi were maximum. For C. gloeosporioides, in rice bran maximum spore count was obtained whereas, in the case of viability of the spores, rice bran and wheat bran were on par. In peat moss none of the fungi grew. In the field tests conducted to try different methods of application of the fungi viz., C. gloeosporioides, F. equiseti, F. semitectum and F. solani, applying bilts of inoculum of the fungi and spraying of the inoculum of the fungi were found to be the best methods. Whereas, dusting of the inoculum produced very poor symptoms. The field performance of the fungi in different carrier materials showed that rice bran and wheat bran inoculum caused good symptom development on water hyacinth plants whereas, coir pith inoculum caused poor symptom development. All the three Fusarium spp. viz., F. equiseti, F. semitectum and F. solani were found to produce toxin. Which could cause similar symptoms on the water hyacinth leaves as those produced by inoculating the culture bits.